Emergent quantum state unveiled by ultrafast collective dynamics in 1 T -TaS 2 - Jiazila Hasaien; Yanling Wu; Mengzhu Shi; Yanni Zhai; Qiong Wu; Zheng Liu; Yi Zhou; Xianhui Chen; Jimin Zhao (Proceedings of the National Academy of Sciences, 2025)
Charge density wave (CDW) material 1 T -TaS 2 was proposed as a quantum spin liquid candidate, on which a cluster Mott insulator comes into being below the transition temperature. We report an experimental ultrafast generation and detection of the coherent amplitude mode (AM) of its CDW state. A salient feature emerges: The coherent CDW mode AM exhibits an unusual T 3.56 temperature dependence below 65 K, in addition to the T 2 temperature dependence observed in the 65 to 200 K range. This behavior suggests the enhancement of in-gap electronic excitations below 65 K and the emergence of a new phase of matter. Consequently, the intriguing quantum state leads to a crossover. Our investigation provides insights into understanding the interplay among various degrees of freedom in quantum materials.